A multivariate statistical index, the fibromyalgia analog model, identifies Dahl S rats as a model of fibromyalgia with improved face validity - Ferrari, Luiz F; Wilkinson, Ashley; Donaldson, Gary W; Shen, Jincheng; Ramirez, Anna; Rey, Charles; Cahoon, Christian; Miner, Dashiell; Okifuji, Akiko; Taylor, Norman E (Pain (Amsterdam), 2025)
Fibromyalgia syndrome (FMS) is clinically diagnosed using a widespread pain index and symptom severity scores. Despite this, multivariate statistical models using clinical data consistently suggest the presence of single overarching factor that can capture much of the variation across a spectrum of biomarkers for FMS, potentially aiding diagnosis. We hypothesized that a comparable single index could be developed for preclinical FMS rat models to quantitatively compare and rigorously test new candidates for improved translational potential and therapeutic screening. We used male and female reserpine-treated Sprague Dawley (SD) rats to produce the fibromyalgia analog model (FAM) index, a tool to systematically determine the robustness of potential models of FMS. Features associated with FMS were assessed by behavior tests, including widespread nociceptive sensitivity evaluated on the hind paws ("paw") and gastrocnemius muscles ("mus") using a Randall-Selitto device, and face ("VF") using von Frey filaments; depression (by the forced swim test [FST]); anxiety (using the Elevated Zero Maze [EZM]); and fatigue (using a Home Cage Monitoring system [HCM]). A multivariate statistical analysis was used to determine the FAM index and document internal and external model validity. The index equation was calculated to be F = 0.410 × rzpaw + 0.618 × rzmus + 0.429 × rzVF + 0.455 × zFST + 0.183 × RZ EZM + 0.160 × rzHCM , where each z is a standardized score. Our data showed the ability of the FAM index to differentiate saline-treated SD rats as a control, "normal" group, vs either acidic saline-injected SD or Dahl S rats as models displaying fibromyalgia-like behaviors.